331 COCHLEAR NERVE DEFICIENCY AS A SIGN OF CHARGE SYNDROME. (1st January 2006) - Carey, J. C.; Park, A.; Dent, K.; Palumbos, J. C.; Clifford, B.; Hedlund, G.
Abstract : The CHARGE syndrome is a distinct pattern of malformation consisting of retinal colobomas, heart malformations, choanal atresia, growth/developmental retardation, genital defects, and ear abnormalities, including sensorineral deafness. Formerly called an association, CHARGE is a discrete enough pattern to be considered a syndrome in the true sense of the term. Recently mutations of the CHD7 g ene have been discovered to account for the majority of patients with this phenotype. Also of note, recent proposals of diagnostic criteria have included vestibular dysplasias, especially absence of the semicircular canals, as a cardinal feature, and have emphasized the inner ear findings of CHARGE. We have evaluated 2 infants with CHARGE who have absence of the cochlear nerve on MRI. The purpose of this paper is to present and discuss these patients. Documentation of these findings helps expand the spectrum on inner ear dysplasias of the syndrome. The 2 unrelated patients, a boy and a girl, both presented to the NICU with multiple congenital anomalies and met criteria for CHARGE: retinal colobomas (2/2), heart malformations (2/2: ASD and ASD/VSD/coart), severe-profound congenital hearing loss (2/2), absence of the semicircular canals (2/2), characteristic external ear (2/2), and micropenis in the boy. Both had normal HRB chromosomes and FISH22 studies. The 2 patients were ascertained as part on the Hearing Assessment Team and are enrolled in the CDC-funded Etiology of Hearing Loss Study. MRI of the temporal regions showed absence of the cochlear nerve (unilateral in 1 patient and bilateral in the other). While cochlear dysplasias and absence of the semicircular canals are well known in CHARGE, cochlear nerve deficiency is not well documented. This finding, along with the other inner ear findings, can support the diagnosis. The otologic manifestations of CHARGE are unique as most syndromes involve the external/middle ear or the inner, not both. Understanding the role of CHD7 i n the pathogenesis of the phenotype may provide insights into inner ear development.